IMPACT OF GOVERNMENT POLICIES ON THE KNOWLEDGE BASE OF SUSTAINABLE SMALL AND MEDIUM-SIZED ENTERPRISES - Yadewani, Dorris; Pandi, Oyyapan Durai; Syafrani, Syafrani; Nurofik, Agus; Poddar, Sandeep (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Small and Medium Enterprises are pivotal in academic research, policy formulation, and economic development because they drive financial growth and create employment opportunities. This study aims to evaluate the factors influencing operational performance in SMEs, focusing on the impact of knowledge and the moderating role of government policies. Utilizing a sample of 200 SME owners in Padang, selected through convenience sampling, data was collected via online questionnaires based on field studies. The analysis, conducted using Structural Equation Modeling-Partial Least Squares, explores the complex relationships between knowledge variables, government policies, and SME operations. Findings reveal that knowledge investment is crucial for the operational success of SMEs, underscoring its importance in business strategy. Government policies also positively influence SME performance, highlighting the need for supportive regulatory environments. This research contributes to a deeper understanding of the factors that support SME success and emphasizes the strategic role of government intervention. The study's novelty lies in its dual focus on knowledge and policy, offering comprehensive insights into their combined effects on SME performance. While the findings are specific to Padang, they suggest broader implications for the role of knowledge and policy in SME development globally. Future research should address the limitations of this study, including its regional focus and variable scope, to enhance our understanding of SME performance on an international scale. This study informs policymakers and SME practitioners and sets the stage for further exploration into the sustainable growth of SMEs worldwide.